(untitled) (Journal of Naval Architecture and Marine Engineering, 2009)
An unsteady 3D surface panel method has been developed to predict hydrodynamic load fluctuations on an ice class propeller induced by continuous variation of proximity to an ice block. The low order, time domain, combined doublet and source panel method approximates the doublet and source distribution uniformly over each panel on the propeller blades. For non-lifting bodies, i.e., the hub and ice block, only sources are distributed over the body surfaces. The simulation model is contrived in such a manner that the ice block and surrounding fluid remain stationary; and at each time step, the propeller rotates and advances forward in the inertial reference frame. This numerical model is validated with previous fixed-proximity experimental measurements and good agreement is obtained. Prediction of the fluctuating hydrodynamic load is carried out as a full dynamic interaction between the ice block and the propeller. Results for this study are compared with previous fixed-proximity numerical models and experiments. The new dynamic model establishes a basis for analysis of a more realistic fluid-structure interaction, which could, in the future, include ice block acceleration due to suction force and ice block impact loading on the propeller blade and shaft. Keywords: Marine Propulsion, Panel Methods, Unsteady Loading, Ice-Propeller Interaction doi: 10.3329/jname.v2i1.2026 Journal of Naval Architecture and Marine Engineering 2(1)(2005) 15-20